Big Book: Scientific literacy of students - Risna, Atikah; Indiyani, Nidya Ayu; Maharani, Desvita Eka; Katri, Anggita Manon; Indriani, Indriani; Sukardi, Rendi Restiana; Sikijip, Fabian bin Fredrick P; Yuniarti, Yeni (Education and Development Research, 2023)
The scientific literacy of students must be enhanced, for it can serve as a foundation for high-quality individual in science. This research's objective is to develop and examine the effect of Big Book on students' scientific literacy. This research is anticipated to provide knowledge and insights regarding the development of Big Book as the media in learning and to enhance the scientific literacy of students. In this research, the Design and Development Research (D&D) method with the ADDIE model was utilized. The results demonstrated that Big Book can be utilized effectively by students. Additionally, students were enthusiastic about learning using Big Book. This shows that the development of Big Book can enhance the scientific literacy of students.